The Myth of Independence - Bhutto, Zulfikar Ali (Lahore Oxford Universtiy Press, 1969)
This book is about Pakistan. With the vigour and vision of one who is both a university intellectual and a practical politician celebrated for is oratory, Mr. Bhutto traces the course of his country's relations with India, the United States, the Soviet Union, China, and many smaller nations.
Includes Epilogue and Illustrations.
Keywords: Pakistan -- Foreign Relations -- Diplomatic Relations